Colorado Tick Fever Virus in the Far West: Forgotten, but Not Gone - Padgett, Kerry A; Kjemtrup, Anne; Novak, Mark; Velez, Jason O; Panella, Nicholas (Vector borne and zoonotic diseases (Larchmont, N.Y.), 2022)
In the past few decades, reported human cases of Colorado tick fever in the western United States have decreased dramatically. The goal of this study was to conduct surveillance for Colorado tick fever virus (CTFV) in ticks in recreational sites in Colorado, Wyoming, and California to determine whether the virus is still present in ticks from these states. Surveillance focused on regions where surveys had been conducted in the 1950s, 1960s, and 1970s. Adult Rocky Mountain wood ticks ( ), Pacific Coast ticks ( ), and winter ticks ( ) were tested by PCR. A subset of PCR-positive ticks ( = 7) were cultured in Vero cells. CTFV-positive Rocky Mountain wood ticks were found in all states: Colorado (58% prevalence), Wyoming (21%), and California (4%). Although no winter ticks tested positive, Pacific Coast ticks tested positive in one county (Siskiyou County, 15% prevalence) and were positive only in a location that also maintained Rocky Mountain wood ticks and golden mantled ground squirrels, a known CTFV host. In summary, CTFV is prevalent in and in regions where they are sympatric in California and in in Colorado and Wyoming. Although the number of human CTFV cases has declined dramatically, this decrease in reported disease does not appear to be due to the disappearance or even the decline in prevalence of this virus in ticks in historically endemic regions of the country.